The effect of an app-based health intervention on somatic symptoms among employees of the DHL Group: a longitudinal pilot study - Naby May; Stefanie Kasten; Thomas Schwan; Matthias Scharle; Andreas Tautz; Stephan Letzel; Pavel Dietz (International Archives of Occupational and Environmental Health, 2025)
Background Somatic symptoms significantly contribute to absenteeism and healthcare costs, particularly in physically demanding professions such as postal and delivery services. The FC-Fit Challenge, an app-based workplace health intervention, aims to promote healthier lifestyles through personalized feedback, social interaction, and professional guidance, targeting lifestyle changes and reducing somatic symptoms. Objectives This study evaluated the effect of the FC-Fit Winterchallenge 2021/22 on somatic symptoms over time, considering sociodemographic and work-related differences, and identified predictors of somatic symptoms to inform workplace health strategies. Methods A longitudinal design with three measurement points was employed: at the start of the intervention (T1), immediately post-intervention (T2), and three-month follow-up (T3). At T1, 497 participants completed the survey. Sociodemographic and work-related variables, health behaviors, and mental health indicators were analyzed. Multiple regression identified significant predictors of somatic symptoms. Results Somatic symptoms significantly decreased post-intervention (T1: 7.0 ± 4.6 vs. T2: 5.9 ± 4.5, p < 0.001), with sustained effects at T3. Women, full-time employees, and administrative staff showed the most pronounced reductions. Predictors of higher somatic symptom severity included female gender, lower education, painkiller use, stress, and burnout, while high physical activity was associated with lower severity. Subgroup analysis revealed variability in intervention effectiveness based on sociodemographic and occupational factors. Conclusions The FC-Fit Challenge is a promising, scalable tool for workplace health promotion. Tailoring interventions to specific employee profiles and addressing predictors like stress and burnout can optimize outcomes. Future studies should target underrepresented groups, such as delivery workers, and use randomized controlled designs to validate findings.

Correction to: Self‑reported cardiovascular health of teachers: results from the 5‑year follow‑up of the Gutenberg Health Study cohort - Merle Riechmann‑Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)

Self-reported cardiovascular health of teachers: results from the 5-year follow-up of the Gutenberg Health Study cohort - Merle Riechmann-Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives Following an exploratory approach, we examined cardiovascular disease risk factors at baseline and the 5-year incidence proportion of self-reported doctor-diagnosed cardiovascular diseases (CVD) in teachers and other occupational groups of the Gutenberg Health Study. Methods Study participants lived in the region of Mainz, Germany. Data from 6510 working participants without prevalent CVD at baseline (2007–2012) were analyzed. Participants were teachers ( n = 215), other professionals from the health, social or educational (HSE) fields ( n = 1061) or worked outside the HSE fields ( n = 5234). For occupational comparisons, we estimated prevalence ratios (PR) for each CVD risk factor at baseline with robust Poisson regression analyses. We calculated crude CVD incidence rates based on the observed 5-year CVD cumulative incidence at follow-up and estimated age-weighted incidence proportions. All analyses were stratified by sex. Results Male non-HSE workers showed a higher prevalence of smoking and physical inactivity than male teachers (PR 2.26; 95%-CI: 1.06–4.82/PR 1.89; 95%-CI: 1.24–2.87). In contrast, non-HSE workers and other HSE professionals were less likely to have reported an unhealthy alcohol intake than teachers. Differences were attenuated after SES-adjustment. We did not detect occupational group-specific differences in CVD incidence. However, there were only two cases of CVD among the teachers. Conclusion Particularly male teachers showed a healthier lifestyle regarding physical inactivity and smoking. Nevertheless, occupational-medical care practitioners and researchers need to be aware of the relatively heightened prevalence of unhealthy alcohol intake in female and male teachers, and in absolute terms, the high hypertension prevalence in male teachers.

Liquid release as a source of potential drug exposure during the handling of intravenous infusions in nursing - Verena Segner; Renate Kimbel; Philipp Jochems; André Heinemann; Stephan Letzel; Daniel Wollschläger; Bernd Roßbach (International Archives of Occupational and Environmental Health, 2017)

How can the health situation and well-being of staff at German schools for the severely handicapped be improved? - Matthias Claus; Johanna Adams; Renate Kimbel; Stephan Letzel; Dirk-Matthias Rose (International Archives of Occupational and Environmental Health, 2016)

Development of a mobbing short scale in the Gutenberg Health Study - Susan Garthus-Niegel; Matthias Nübling; Stephan Letzel; Janice Hegewald; Mandy Wagner; Philipp S. Wild; Maria Blettner; Isabella Zwiener; Ute Latza; Sylvia Jankowiak; Falk Liebers; Andreas Seidler (International Archives of Occupational and Environmental Health, 2016)

Biological monitoring of occupational exposure to polycyclic aromatic hydrocarbons (PAH) by determination of monohydroxylated metabolites of phenanthrene and pyrene in urine - Bernd Rossbach; Ralf Preuss; Stephan Letzel; Hans Drexler; Jürgen Angerer (International Archives of Occupational and Environmental Health, 2007)